HARLIN model for prediction of solar radiation for Baghdad city, Iraq - Ajil, Awras H. (Iraqi Journal of Science, 2022)
In this study a combination of two basics known methods used to daily prediction of solar insolation in Baghdad city, Iraq, for the first time, the harmonic and the classical linear regression analyses, thus it is called HARLIN model. The resulted prediction data compared with basics data for Baghdad city for two years (2010-2011), where the model showed a great success application in the accurate results, compared with the linear famous and well known model which is used the classical linear Angstrom equations with various formulations in many previous studies.